2008
DOI: 10.3354/dao01893
|View full text |Cite
|
Sign up to set email alerts
|

Background pathology of the ovary in a laboratory population of zebrafish Danio rerio

Abstract: Adult zebrafish Danio rerio originating from one stock used as control animals in a toxicological study were examined histopathologically for the occurrence of spontaneous lesions in the gonads. While no histopathological changes were seen in the testes, the ovaries showed lesions consisting mainly of acute granulomatous inflammation with increased atresia and the presence of egg debris in the ovarian parenchyma and in the oviduct. Since infectious agents could not be detected and the fish were not exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Although ovaries with this condition may be infected with mycobacteria (Whipps et al 2008), many cases are not associated with readily detectable infectious agents (Rossteuscher et al 2008). In one zebrafish study, increased atresia (degeneration) of mature eggs was statistically correlated with the occurrence of egg debris (Rossteucher et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ovaries with this condition may be infected with mycobacteria (Whipps et al 2008), many cases are not associated with readily detectable infectious agents (Rossteuscher et al 2008). In one zebrafish study, increased atresia (degeneration) of mature eggs was statistically correlated with the occurrence of egg debris (Rossteucher et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although ovaries with this condition may be infected with mycobacteria (Whipps et al 2008), many cases are not associated with readily detectable infectious agents (Rossteuscher et al 2008). In one zebrafish study, increased atresia (degeneration) of mature eggs was statistically correlated with the occurrence of egg debris (Rossteucher et al 2008). The authors of that investigation concluded that the associated inflammatory changes could be caused either by primary inflammation followed by increased atresia, or conversely, by a secondary inflammatory response to the presence of egg debris.…”
Section: Introductionmentioning
confidence: 99%
“…12,15 In a report of zebrafish ovarian pathology, EAI was found in 42% of 59 3-mo-old fish. 22 Although EAI was higher in our fish (93%), this may be partly attributable to their Table 3. Histologic changes for each MS222 storage condition for acute (24 h) and chronic (2 wk) timepoints.…”
Section: Discussionmentioning
confidence: 66%
“…Also, fish exposed to this high concentration experienced an increase in oocyte atresia. Follicular atresia can be a natural degenerative process , often occurring spontaneously in zebrafish , as evidenced by the common incidence of the finding in control fish . It can also be indicative of having reached a systemic level of toxicity or stress .…”
Section: Discussionmentioning
confidence: 99%